Effectiveness of a Fishway for Restoring Passage of Colorado River Cutthroat Trout. (6th November 2017) - Hodge, Brian W.; Fetherman, Eric R.; Rogers, Kevin B.; Henderson, Richard
Abstract: Little is known about the effectiveness of fishways for restoring passage to inland (nonanadromous) salmonids. We used PIT telemetry to evaluate the biological effectiveness of a vertical‐slot fishway constructed to restore passage of adult Colorado River Cutthroat Trout Oncorhynchus clarkii pleuriticus (CRCT) in a small Rocky Mountain stream. Our objectives were to assess (1) fishway efficacy (whether or not the fishway restored fish passage), (2) approach efficiency (the probability that a tagged fish encountered the fishway; an index of population use), (3) attraction efficiency (the probability that a fish near the fishway located its entrance), and (4) passage efficiency (the probability that a fish entering the fishway navigated successfully through it). To account for antenna detection probabilities and avoid biases that can result from simple, proportion‐based calculations, we used a variation of the Cormack–Jolly–Seber model to derive efficiency estimates. The fishway restored passage of adult CRCT to long‐vacant habitats. Approach efficiency was 4%; attraction and passage efficiencies were 100%. We conclude that fishways can effectively restore passage of inland salmonids, and we recommend that additional fishway monitoring studies be conducted to inform decision‐making and elucidate which designs and conditions will best facilitate passage. Received April 19, 2017; accepted September 26, 2017Published online November 6, 2017